MODERATING ROLE OF SOCIAL SUPPORT IN THE RELATIONSHIP BETWEEN PERCEIVED JOB INSECURITY AND MENTAL WELL-BEING AMONG ACADEMIC STAFF - Ahamefule, Kenneth N.; Ofoke, M. Sunday; Nwangele, M. Laurence; Odoh, P. Ogechukwu; Nwambam, Dennis I (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
This study investigated the relationship between job insecurity and mental well-being and how social support moderates the relationship. The study adopted a cross-sectional survey design and a total of 200 academic staff were drawn through stratified random sampling techniques from King David Federal University, Uburu. The participants age ranged from 22 to 70 years with a mean age of 37 .86 years and SD = 7 .92 years. The instruments for data collection include: Job insecurity scale, mental well-being scale and social support inventory. Hayes PROCESS macro for SPSS (Model 1) was used as statistical tools for data analysis and test of hypotheses. Results showed that job insecurity was statistically and significant negative relationship with mental well-being (r = −0.04, p < 0 .001), and social support had a statistical and significant positive relationship with mental well-being (r = 0 .07, p < 0 .001). Results also revealed an interactive effect on the role of job insecurity and social support on mental well-being was also significant (β=0.41, P<0.001). The study concluded that social support serves as an important personal resource that can buffer the adverse mental and psychological effects of job insecurity and mental health of academic staff, indicating higher social support are better equipped to maintain their mental well-being despite uncertain employment conditions. The study recommends that an integration of social support into staff development welfare as this could buffer the negative effect of job insecurity and enhance psychological resilience and mental well-being of employees.